Spatiotemporal stability of management zones in a table grapes vineyard in Greece. (1st June 2017) - Anastasiou, E.; Tsiropoulos, Z.; Balafoutis, T.; Fountas, S.; Templalexis, C.; Lentzou, D.; Xanthopoulos, G.
Abstract : Research on precision viticulture on table grapes is relative new compared to wine grapes. The aim of this study was to assess the spatiotemporal stability of yield and quality components in a vineyard of table grapes. The study was conducted in a commercial vineyard (1.4 ha) of table grapes for two successive cultivation years 2015 and 2016. Yield and quality parameters were assessed using destructive and non-destructive methods. The preliminary results revealed that spatiotemporal stability of management zones is affected by weather conditions and is different for each crop parameter, while NDVI presented good performance for delineating management zones.